MnZn-BASED FERRITE
The tailored MnZn-based ferrite composition addresses the challenge of maintaining high incremental magnetic permeability across a wide temperature range and under varying DC fields, achieving desired permeabilities for automotive and PoE applications.
Patent Information
- Application Number
- JP2024178257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Existing MnZn-based ferrites for pulse transformers face challenges in maintaining high incremental magnetic permeability over a wide temperature range (-50 to 150°C) and under varying DC magnetic fields, especially in automotive and PoE power supply applications, where conventional materials fail to achieve permeabilities of 2300 or more and 1000 or more, respectively.
A specific composition of MnZn-based ferrite is formulated with controlled amounts of Fe2O3, ZnO, MnO, and additional subcomponents like SiO2, CaO, Co3O4, TiO2, Nb2O5, and V2O5, optimized to maintain high incremental magnetic permeability across a broad temperature range and under different DC magnetic field strengths.
The optimized MnZn-based ferrite achieves incremental magnetic permeabilities of 2300 or more under a 25 A/m DC field from -50 to 150°C and 1000 or more at 125°C when a 50 A/m field is applied, enhancing stability and performance in extreme conditions.
Smart Images

Figure 2025010163000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an MnZn-based ferrite, and more particularly to an MnZn-based ferrite suitable for electronic components such as pulse transformers. [Background technology]
[0002] For the transformers of Ethernet (registered trademark) devices, pulse transformers with soft magnetic material in the magnetic core are used for the purpose of matching impedance at the input / output terminals, maintaining electrical insulation, etc. Pulse transformers have high inductance, i.e., high incremental permeability (μ Δ ) Here, incremental permeability is a value that indicates the permeability (ease of magnetization) of a magnetic core when a magnetic field is applied. Note that incremental permeability and effective permeability are synonymous, so in this specification they will be consistently referred to as incremental permeability.
[0003] Toroidal MnZn ferrite is generally used for magnetic cores using soft magnetic materials. Among many soft magnetic materials, MnZn ferrite is particularly easy to obtain high magnetic permeability and high inductance, and has other features such as being inexpensive compared to metallic magnetic materials such as amorphous metals, and being an oxide, it does not rust and is stable.
[0004] However, since MnZn-based ferrite is an oxide magnetic material, its Curie temperature is not high and its magnetic properties change significantly with temperature fluctuations. As a result, it has the disadvantage that it is difficult to obtain stable magnetic properties over a wide temperature range compared to metal magnetic materials.
[0005] Pulse transformers may be installed outdoors when used in line termination devices, etc., and the MnZn ferrite used in pulse transformers is required to have a high initial permeability (μi) over a wide temperature range from low to high. In addition, in digital communication devices, the pulse transformer may be magnetized due to fluctuations in the positive / negative balance of the transmitted pulse voltage, and may operate when a DC magnetic field is applied. Even when such a DC magnetic field is applied, a high inductance is required for signal conversion, i.e., a high incremental permeability. In the above-mentioned applications, the magnitude of the DC magnetic field applied varies depending on the required inductance standard and usage, but a high incremental permeability is required at room temperature.
[0006] Conventionally, pulse transformers have been widely used in consumer devices, but in recent years, as car networking has progressed, they are also being used more in automobiles. Conventional consumer devices were required to operate normally within temperature ranges such as 0 to 70°C, -40 to 85°C, or -40 to 105°C, but automotive applications require normal operation within a wider temperature range, such as -40 to 125°C or -50 to 150°C.
[0007] On the other hand, there are also applications for power over Ethernet (PoE) power supply such as PoE / PoE+ / PoE++, which directly supplies the driving power of the device along with the transmission signal in Ethernet devices. In this case, the pulse transformer is used under conditions where a current larger than that of the signal transmission is superimposed. Moreover, the peripheral components in the device heat up due to the increase in the output of PoE power supply and the increase in current due to the spread of SiC and GaN semiconductors, so the operating environment of the magnetic core of the pulse transformer is expected to shift to a higher temperature side. Therefore, for the MnZn ferrite used in this application, even if the initial permeability μi is low, a material that can obtain high inductance at higher temperatures and under high magnetic field superposition, i.e., high incremental permeability, is required.
[0008] MnZn-based ferrites used in conventional consumer devices are composed mainly of Fe2O3, ZnO, and MnO, and exhibit high permeability in the main components where the magnetic anisotropy constant and magnetostriction constant are zero. For this reason, MnZn-based ferrites are used as small or thin magnetic cores for transformers, noise filters, etc. Although it is difficult to obtain stable magnetic properties over a wide temperature range, methods have been proposed to achieve high incremental permeability when a DC magnetic field is applied in the temperature range of -40 to 85°C or -40 to 105°C in order to accommodate pulse transformers for consumer applications. In this specification, the values of initial permeability and incremental permeability are all expressed as a ratio (relative permeability) to the vacuum permeability μo.
[0009] Patent Documents 1, 2, and 3 propose ferrites with an incremental permeability of 2000 or more when a DC magnetic field is applied in the temperature range of -40 to 85° C. Patent Documents 4 and 5 propose MnZnCo-based ferrites with high initial permeability in a wide temperature range of about -20 to 150° C. Patent Document 6 proposes MnZn-based ferrites with an initial permeability of 3000 or more at 23° C., a small rate of change in initial permeability from -20 to 150° C., and a saturation magnetic flux density of 540 mT or more at 23° C.
[0010] Patent Document 7 proposes an MnZn ferrite having an incremental permeability of 400 or more in the temperature range of 0° C. to 85° C. and an incremental permeability of 700 or more at 65° C. when a large DC magnetic field of 80 A / m is applied. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2008-143745 A [Patent Document 2] JP 2010-189247 A [Patent Document 3] JP 2010-195596 A [Patent Document 4] JP 2015-229625 A [Patent Document 5] JP 2015-229626 A [Patent Document 6] JP 2005-236069 A [Patent Document 7] JP 2010-173899 A Summary of the Invention [Problem to be solved by the invention]
[0012] However, the temperature range assumed in Patent Documents 1, 2, and 3 is -40 to 85°C, and an incremental permeability of 2300 or more cannot be obtained in the temperature range of -50 to 150°C. Although the temperature range assumed in Patent Documents 4 and 5 is wide, the MnZnCo-based ferrites in Patent Documents 4 and 5 are for noise filters, and the incremental permeability when a DC magnetic field is applied is not taken into consideration, and it is impossible to obtain an incremental permeability of 2300 or more in the temperature range of -50 to 150°C. Patent Document 6 describes that the rate of change of the initial permeability is small in the temperature range of -20 to 150°C, but the incremental permeability when a DC magnetic field is applied is not taken into consideration, and it is impossible to obtain an incremental permeability of 2300 or more in the temperature range of -50 to 150°C.
[0013] In Patent Document 7, even though a large DC magnetic field of 80 A / m is applied, the incremental permeability at 85°C is less than 1000 in all cases, and it is impossible to obtain an incremental permeability of a practical level of 1000 or more in a temperature range exceeding 85°C.
[0014] To date, many MnZn-based ferrites have been proposed for pulse transformers suitable for consumer devices that can be used in a temperature range of -40 to 85°C. However, no MnZn-based ferrites have been proposed that have excellent incremental permeability when a DC magnetic field is applied over a wide temperature range and are suitable for LANs for automotive applications that can be used in a temperature range of -50 to 150°C.
[0015] Moreover, there has been no proposal for an MnZn-based ferrite that provides a high incremental permeability when a DC magnetic field of 50 A / m is applied, which is suitable for PoE power supply that can be used in a temperature range exceeding 85°C.
[0016] Therefore, an object of the present invention is to provide an MnZn-based ferrite having a high incremental permeability over a wide temperature range, i.e., an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150° C. Another object of the present invention is to provide an MnZn-based ferrite having an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125° C.
[0017] In general, the incremental permeability of MnZn ferrite is measured by applying a DC magnetic field of 25 A / m, but there are special cases where a DC magnetic field of 33 A / m is applied depending on the application of the MnZn ferrite, as in Patent Documents 1, 2, and 3. In the present invention, the DC magnetic field applied when measuring the incremental permeability of MnZn ferrite for general use is 25 A / m. Also, the DC magnetic field applied when measuring the incremental permeability of MnZn ferrite for PoE power supply is 50 A / m. [Means for solving the problem]
[0018] The present inventors conducted extensive research to solve the above problems, and have come to the following findings: By containing predetermined amounts of Fe and Zn as basic components, the remainder being Mn, and predetermined amounts of Si, Ca, Co, Ti, Nb, and V as minor components, the incremental permeability can be made 2300 or more when a direct current magnetic field of 25 A / m is applied in the temperature range of -50 to 150°C. Also, the incremental permeability can be made 1000 or more when a direct current magnetic field of 50 A / m is applied at 125°C.
[0019] The present invention, which has been completed based on the above findings, has the following essential features.
[0020] [1] A MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are calculated as Fe2O3, ZnO, and MnO, respectively, with the total of Fe, Zn, and Mn being 100.0 mol%, Fe: 52.6 mol% or more and 53.6 mol% or less in terms of Fe2O3 Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si: 30 mass ppm or more and 200 mass ppm or less in terms of SiO2; Ca: 300 mass ppm or more and 1000 mass ppm or less in terms of CaO; Co: 2100 mass ppm or more and 3500 mass ppm or less in terms of Co3O4, Ti: 2500 mass ppm or more and 4000 mass ppm or less in terms of TiO2; Nb: 50 mass ppm or more and 500 mass ppm or less in terms of Nb2O5, and V: 0 ppm to 500 ppm by mass calculated as V2O5 MnZn ferrite consisting of
[0021] [2] A MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are calculated as Fe2O3, ZnO, and MnO, respectively, with the total of Fe, Zn, and Mn being 100.0 mol%, Fe: 52.0 mol% or more and 53.6 mol% or less in terms of Fe2O3 Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si: 30 mass ppm or more and 200 mass ppm or less in terms of SiO2; Ca: 300 mass ppm or more and 1000 mass ppm or less in terms of CaO; Co: 2100 mass ppm or more and 2700 mass ppm or less in terms of Co3O4, Ti: 2500 mass ppm or more and 4000 mass ppm or less in terms of TiO2; Nb: 50 mass ppm or more and 500 mass ppm or less in terms of Nb2O5, and V: 0 ppm to 500 ppm by mass calculated as V2O5 MnZn ferrite consisting of
[0022] [3] A MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are calculated as Fe2O3, ZnO, and MnO, respectively, with the total of Fe, Zn, and Mn being 100.0 mol%, Fe: 52.6 mol% or more and 53.6 mol% or less in terms of Fe2O3 Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si: 30 mass ppm or more and 200 mass ppm or less in terms of SiO2; Ca: 300 mass ppm or more and 1000 mass ppm or less in terms of CaO; Co: 2100 mass ppm or more and 2700 mass ppm or less in terms of Co3O4, Ti: 2500 mass ppm or more and 4000 mass ppm or less in terms of TiO2; Nb: 50 mass ppm or more and 500 mass ppm or less in terms of Nb2O5, and V: 0 ppm to 500 ppm by mass calculated as V2O5 MnZn ferrite consisting of
[0023] [4] The MnZn-based ferrite according to any one of the above [1] to [3], having a V content in terms of V2O5 of 50 ppm by mass or more and 250 ppm by mass or less.
[0024] [5] The MnZn-based ferrite according to any one of the above [1] to [3], having a V content in terms of V2O5 of 100 ppm by mass or more and 500 ppm by mass or less.
[0025] [6] The MnZn-based ferrite according to any one of the above [1] to [4], which has an incremental permeability of 2300 or more when a direct current magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C.
[0026] [7] The MnZn-based ferrite according to any one of the above [1] to [3] and [5], which has an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125° C. Effect of the Invention
[0027] According to the present invention, it is possible to obtain an MnZn-based ferrite having a high incremental permeability over a wide temperature range, i.e., an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in the temperature range of -50 to 150° C. Also, according to the present invention, it is possible to obtain an MnZn-based ferrite having an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125° C. [Brief description of the drawings]
[0028] [Figure 1A] 1 is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in examples and comparative examples of the present invention. Fig. 1A shows examples and comparative examples in which the content of Fe, which is a basic component, is changed. [Figure 1B] 1 is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in an example of the present invention and a comparative example. FIG 1B shows an example of the present invention and a comparative example in which the content of Zn, which is a basic component, is changed. [Figure 2A] 2 is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in an example of the present invention and a comparative example. FIG 2A shows an example of the present invention and a comparative example in which the content of Si, which is a subcomponent, is changed. [Figure 2B] 2B is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in the examples and comparative examples of the present invention. FIG. 2B shows examples and comparative examples in which the content of Ca, which is a subcomponent, is changed. [Figure 2C]2C is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in an example of the present invention and a comparative example. FIG. 2C shows an example of the present invention and a comparative example in which the content of Co, which is a subcomponent, is changed. [Figure 2D] 2A is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in the examples and comparative examples of the present invention. FIG. 2D shows examples and comparative examples in which the content of Ti, which is a subcomponent, is changed. [Figure 2E] 2B is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in the examples and comparative examples of the present invention. FIG. 2E shows examples and comparative examples in which the content of Nb, which is a subcomponent, is changed. [Diagram 3] 3 is a graph showing incremental permeability when a DC magnetic field of 25 A / m is applied in the temperature range of −50 to 150° C. in the examples of the present invention and comparative examples. FIG. 3 shows examples of the present invention and comparative examples in which the content of V, which is a subcomponent, is changed. [Figure 4A] 4 is a graph showing incremental permeability when a DC magnetic field of 50 A / m is applied in the temperature range of −50 to 125° C. in examples and comparative examples of the present invention. Fig. 4A shows examples and comparative examples in which the content of Ca, which is a subcomponent, is changed. [Figure 4B] 4 is a graph showing incremental permeability when a DC magnetic field of 50 A / m is applied in the temperature range of −50 to 125° C. in the examples and comparative examples of the present invention. FIG. 4B shows examples and comparative examples in which the content of V, which is a subcomponent, is changed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, an embodiment of the MnZn ferrite according to the present invention will be described. Note that the embodiment described below is an example of the present invention, and the configuration of the present invention is not limited to this specific example.
[0030] [MnZn ferrite] The MnZn ferrite according to the present invention is composed of basic components, subcomponents and unavoidable impurities, and the basic components are oxides of Fe, Zn and Mn. Note that the following mol% is the composition ratio in the basic components.
[0031] (Main component) Fe2O3: 52.0mol% to 53.6mol% When the Fe content of the MnZn ferrite is less than 52.0 mol% in terms of Fe2O3, the incremental permeability is greatly reduced. Therefore, the Fe content of the MnZn ferrite is 52.0 mol% or more in terms of Fe2O3, and preferably 52.6 mol% or more. On the other hand, when the Fe content of the MnZn ferrite is more than 53.6 mol% in terms of Fe2O3, the incremental permeability is also greatly reduced. Therefore, the Fe content of the MnZn ferrite is 53.6 mol% or less in terms of Fe2O3, and preferably 53.1 mol% or less. When the Fe content of the MnZn ferrite is about 53.0 mol% in terms of Fe2O3, the magnetostriction constant λ becomes 0, and the incremental permeability when a DC magnetic field is applied is the highest. It is believed that as the Fe content deviates from the case where Fe is 53.0 mol% calculated as Fe2O3, i.e., from the case where λ = 0, the applied magnetic field causes the core to expand and contract and deform, resulting in stress, which in turn inhibits domain wall motion and significantly reduces the incremental permeability.
[0032] ZnO: 10.1 mol% or more and less than 13.0 mol% It is known that the Curie temperature and secondary peak of MnZn ferrite change depending on the ratio of Fe to Zn. If the Zn content is 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, the Curie temperature is generally 200°C or more, and a high incremental permeability can be obtained up to a high temperature range of 150°C. If the Zn content of MnZn ferrite is less than 10.1 mol% in terms of ZnO, the Curie temperature is high, but the initial permeability when no DC magnetic field is applied decreases, and as a result, the incremental permeability when a DC magnetic field is applied also decreases over the entire temperature range. Therefore, the Zn content of MnZn ferrite is 10.1 mol% or more in terms of ZnO, preferably 10.2 mol% or more, more preferably 10.5 mol% or more, and even more preferably 11.0 mol% or more. On the other hand, when the Zn content in the MnZn ferrite is 13.0 mol% or more calculated as ZnO, the initial permeability increases when no DC magnetic field is applied, but the Curie temperature decreases, and the incremental permeability decreases when a DC magnetic field is applied at 150° C. Therefore, the Zn content in the MnZn ferrite is less than 13.0 mol% calculated as ZnO, and is preferably 12.9 mol% or less.
[0033] The Curie temperature of the MnZn ferrite according to the present invention is preferably 190° C. or higher, and more preferably 200° C. or higher, in order to obtain a high incremental permeability when a DC magnetic field is applied even at 150° C. The Curie temperature of the MnZn ferrite does not have an upper limit, but is generally 230° C. or lower.
[0034] MnO: remainder In the MnZn ferrite according to the present invention, the total amount of Fe2O3, ZnO, and MnO is 100.0 mol%. The Mn contained in the MnZn ferrite is preferably 33.9 mol% or more calculated as MnO. The Mn contained in the MnZn ferrite is preferably 37.0 mol% or less, more preferably 36.9 mol% or less, calculated as MnO.
[0035] (Secondary ingredient) Next, the auxiliary components will be described. The MnZn ferrite according to the present invention contains Si, Ca, Co, Ti, and Nb as auxiliary components in addition to the above basic components. It is preferable that the MnZn ferrite further contains V as an auxiliary component. These are present in the MnZn ferrite as oxides such as SiO2, CaO, Co3O4, TiO2, Nb2O5, and V2O5. The auxiliary components of the composition of the present invention are preferably composed of SiO2, CaO, Co3O4, TiO2, and Nb2O5, or preferably composed of SiO2, CaO, Co3O4, TiO2, Nb2O5, and V2O5. In the present invention, the content of the auxiliary components is the content relative to the basic components.
[0036] SiO2: 30 mass ppm or more and 200 mass ppm or less SiO2 is an additive that promotes the formation of grain boundaries, inhibits grain growth, increases resistivity, and decreases initial permeability. By adding an appropriate amount of SiO2 to MnZn ferrite, the incremental permeability can be increased in a wide temperature range of -50 to 150°C. If the Si content of MnZn ferrite is less than 30 mass ppm in terms of SiO2, the incremental permeability in low and high temperature ranges decreases, and it becomes difficult to obtain an incremental permeability of 2300 or more when a DC magnetic field is applied in a wide temperature range of -50 to 150°C. Therefore, the Si content of MnZn ferrite is 30 mass ppm or more in terms of SiO2, preferably 32 mass ppm or more, and more preferably 35 mass ppm or more. On the other hand, when the Si contained in the MnZn-based ferrite exceeds 200 ppm by mass in terms of SiO2, the initial permeability is significantly reduced, and accordingly the incremental permeability is also significantly reduced, making it difficult to obtain an incremental permeability of 2300 or more in the wide temperature range of -50 to 150°C. Therefore, the Si contained in the MnZn-based ferrite is set to 200 ppm by mass or less in terms of SiO2, preferably 190 ppm by mass or less, more preferably 150 ppm by mass or less, and even more preferably 49 ppm by mass or less.
[0037] CaO: 300 mass ppm or more and 1000 mass ppm or less CaO is an additive that promotes the formation of grain boundaries, inhibits grain growth, increases resistivity, and decreases initial permeability. However, by adding an appropriate amount of CaO to MnZn ferrite, the incremental permeability can be increased in a wide temperature range of -50 to 150°C. If the Ca content of MnZn ferrite is less than 300 mass ppm in terms of CaO, the incremental permeability in low and high temperature ranges decreases, and it becomes difficult to obtain an incremental permeability of 2300 or more when a DC magnetic field is applied in a wide temperature range of -50 to 150°C. Therefore, the Ca content of MnZn ferrite is 300 mass ppm or more, and preferably 390 mass ppm or more, in terms of CaO. On the other hand, when the Ca content in the MnZn ferrite exceeds 1000 ppm by mass calculated as CaO, the initial permeability is significantly reduced, and accordingly the incremental permeability is also significantly reduced, making it difficult to obtain an incremental permeability of 2300 or more in the wide temperature range of -50 to 150°C. Therefore, the Ca content in the MnZn ferrite is set to 1000 ppm by mass or less, preferably 950 ppm by mass or less, and more preferably 840 ppm by mass or less, calculated as CaO.
[0038] In MnZn-based ferrite for PoE power supply applications, where the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C is important, the more Ca contained, the higher the incremental permeability can be obtained. Therefore, in MnZn-based ferrite for PoE power supply applications, the Ca contained in the MnZn-based ferrite is preferably 500 mass ppm or more, more preferably 600 mass ppm or more, even more preferably 700 mass ppm or more, and most preferably 800 mass ppm or more, calculated as CaO.
[0039] On the other hand, when the Ca content of the MnZn ferrite exceeds 1000 ppm by mass in terms of CaO, the initial permeability decreases excessively, and the incremental permeability also decreases accordingly, so that the incremental permeability when a direct current magnetic field of 50 A / m is applied at 125°C falls below 1000, which is undesirable. Therefore, even in the case of MnZn ferrite for PoE power supply, the Ca content of the MnZn ferrite is preferably 1000 ppm by mass or less, and more preferably 950 ppm by mass or less, in terms of CaO.
[0040] Co3O4: 2100 mass ppm or more and 3500 mass ppm or less Co3O4 is an effective additive for improving the temperature dependence of the magnetic properties of MnZn ferrite. When MnZn ferrite contains an appropriate amount of Co3O4, the change in the incremental permeability with respect to temperature when a DC magnetic field is applied is reduced, and the incremental permeability in the low and high temperature ranges is improved. However, since Co3O4 also has the function of shifting the temperature dependence of the permeability to the low temperature side, if the Co content is too small or too large, the balance of the permeability in the low and high temperature ranges is lost, the incremental permeability in the low or high temperature range decreases, and a high incremental permeability cannot be obtained in a wide temperature range of -50 to 150°C. If the Co content of the MnZn ferrite is less than 2100 mass ppm in terms of Co3O4, the maximum point of the temperature characteristic of the incremental permeability shifts to the high temperature side, and although the incremental permeability at high temperatures is high, the characteristics at low temperatures become poor, and it becomes impossible to obtain an incremental permeability of 2300 or more in a wide temperature range of -50 to 150°C. Therefore, the Co contained in the MnZn ferrite is 2100 mass ppm or more, preferably 2300 mass ppm or more, calculated as Co3O4. On the other hand, if the Co contained in the MnZn ferrite exceeds 3500 mass ppm, calculated as Co3O4, the maximum point of the temperature characteristic of the incremental permeability shifts to the low temperature side, and although the low temperature characteristic of the incremental permeability is improved, the high temperature characteristic is deteriorated, and it becomes impossible to obtain an incremental permeability of 2300 or more in a wide temperature range of -50 to 150°C. Therefore, the Co contained in the MnZn ferrite is 3500 mass ppm or less, preferably 3200 mass ppm or less, calculated as Co3O4.
[0041] TiO2: 2500 mass ppm or more and 4000 mass ppm or less TiO2 is an effective additive for increasing the incremental permeability of MnZn ferrite when a DC magnetic field is applied. TiO2 does not have much effect on the size of the crystal grains of ferrite, but by containing an appropriate amount of TiO2, the coercive force of ferrite decreases, and the gradient of the demagnetization curve changes in the region where a magnetic field equivalent to a DC magnetic field of 25 A / m is applied, thereby increasing the incremental permeability. However, since TiO2 also acts to shift the temperature characteristics of the initial permeability and incremental permeability to the low temperature side, if the content is not appropriate, the low temperature and high temperature characteristics will deteriorate, and it will be impossible to obtain an incremental permeability of 2300 or more in the wide temperature range of -50 to 150 °C. If the Ti contained in the MnZn ferrite is less than 2500 mass ppm in terms of TiO2, the increase in incremental permeability is insufficient and the temperature characteristics will also shift to the high temperature side, making it impossible to obtain an incremental permeability of 2300 or more in the wide temperature range of -50 to 150 °C. Therefore, the Ti contained in the MnZn ferrite is 2500 mass ppm or more in terms of TiO2, preferably 2650 mass ppm or more, and more preferably 2800 mass ppm or more. On the other hand, when the Ti contained in the MnZn ferrite exceeds 4000 mass ppm in terms of TiO2, the temperature characteristic shifts to the low temperature side, and in the temperature range around -50°C, the incremental permeability when a DC magnetic field is applied also drops sharply for an unknown reason, so that an incremental permeability of 2300 or more cannot be obtained. Therefore, the Ti contained in the MnZn ferrite is 4000 mass ppm or less in terms of TiO2, preferably 3950 mass ppm or less, more preferably 3500 mass ppm or less, and even more preferably 3300 mass ppm or less.
[0042] Nb2O5: 50 mass ppm or more and 500 mass ppm or less Nb2O5 has the effect of suppressing the generation of coarse crystal grains, obtaining fine and uniform crystal grains, and increasing the resistivity. By containing an appropriate amount of Nb, the incremental permeability when a DC magnetic field is applied can be increased. If the Nb contained in the MnZn ferrite is less than 50 mass ppm in terms of Nb2O5, the suppression of the generation of coarse crystal grains is not sufficient, and the resistivity is also low, so the incremental permeability when a DC magnetic field is applied also decreases. Therefore, the Nb contained in the MnZn ferrite is 50 mass ppm or more in terms of Nb2O5, preferably 75 mass ppm or more, more preferably 100 mass ppm or more, and even more preferably 130 mass ppm or more. On the other hand, if the Nb contained in the MnZn ferrite exceeds 500 mass ppm in terms of Nb2O5, the crystal grains become fine and the resistivity increases, so that the magnetic domain walls are less likely to move and the initial permeability decreases. Therefore, the amount of Nb contained in the MnZn-based ferrite is 500 ppm by mass or less, preferably 475 ppm by mass or less, and more preferably 400 ppm by mass or less, calculated as Nb2O5.
[0043] V2O5: 0 mass ppm or more and 500 mass ppm or less Like Nb2O5, V2O5 is an additive that suppresses the generation of coarse crystal grains, obtains fine and uniform crystal grains, and has the effect of increasing the resistivity. By containing Nb and an appropriate amount of V, the incremental permeability when a DC magnetic field is applied can be suitably increased. Therefore, in general applications in the temperature range of -50 to 150°C, the V2O5 contained in the MnZn ferrite is 0 mass ppm or more, preferably 50 mass ppm or more, and more preferably 55 mass ppm or more. In addition, in PoE power supply applications in which the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C is important, the V2O5 contained in the MnZn ferrite is 0 mass ppm or more, preferably 100 mass ppm or more, and more preferably 150 mass ppm or more.
[0044] On the other hand, in any application, when the V contained in the MnZn-based ferrite exceeds 500 mass ppm in terms of V2O5, the crystal grains become fine and the resistivity increases, so that the domain walls are difficult to move and the initial permeability decreases. As a result, the incremental permeability also decreases. Therefore, the V2O5 contained in the MnZn-based ferrite for general use is 500 mass ppm or less, preferably 490 mass ppm or less, more preferably 480 mass ppm or less, and even more preferably 250 mass ppm or less. In addition, the V2O5 contained in the MnZn-based ferrite for PoE power supply is 500 mass ppm or less, preferably 400 mass ppm or less.
[0045] (Inevitable impurities) The composition of the MnZn-based ferrite of the present invention is composed of inevitable impurities other than the basic components and the subcomponents. Examples of inevitable impurities include P, B, S, Cl, and K, and the total content of these inevitable impurities is suppressed to 500 mass ppm or less. The total content of inevitable impurities is preferably 100 mass ppm or less, and more preferably 50 mass ppm or less.
[0046] (Initial permeability when no DC magnetic field is applied) When a DC magnetic field is applied to MnZn ferrite, the initial permeability decreases, that is, the incremental permeability also decreases. Therefore, in order to obtain a high incremental permeability, it is important to keep the initial permeability high when no DC magnetic field is applied. In the case of MnZn ferrite for general use in the temperature range of -50 to 150 ° C, if the initial permeability at 23 ° C when no DC magnetic field is applied is 3500 or more, a high incremental permeability of 2300 or more can be suitably obtained in a wide temperature range of -50 to 150 ° C. Therefore, it is preferable that the initial permeability of MnZn ferrite at 23 ° C when no DC magnetic field is applied is 3500 or more. On the other hand, there is no particular upper limit to the initial permeability at 23 ° C when no DC magnetic field is applied, but it is generally 5000 or less.
[0047] (Incremental permeability when a DC magnetic field of 25A / m is applied in the temperature range of -50 to 150°C) By having the above composition, the MnZn ferrite can have an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. There is no particular upper limit to the incremental permeability when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C, but it is generally 4500 or less.
[0048] (Incremental permeability when a DC magnetic field of 50A / m is applied at 125℃, for PoE power supply) In MnZn ferrite, the incremental permeability drops significantly especially at high temperatures when a DC magnetic field is applied, but by having the above composition, MnZn ferrite can have an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125°C. There is no particular upper limit to the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C, but it is generally 2000 or less.
[0049] [Manufacturing method of MnZn ferrite] Next, a method for producing the MnZn-based ferrite according to the present invention will be described. As the method for producing the MnZn-based ferrite according to the present invention, a known general production method can be used.
[0050] An example of the method for producing MnZn-based ferrite according to the present invention is as follows. First, the powder raw materials of the main components Fe2O3, ZnO and Mn3O4 (the composition ratio is converted to MnO, not Mn3O4) are weighed to have the content specified in the present invention, and mixed in an attritor or ball mill to obtain a mixed powder. The mixing method may be either a dry method or a wet method. Then, the mixed powder is calcined at 800 to 1000°C to obtain a calcined powder. Next, the calcined powder obtained is wet-pulverized in an attritor or ball mill and pulverized until the particle size is about 0.8 to 1.6 μm to obtain a pulverized powder. At this time, oxides of the subcomponents are added and pulverized to have the content specified in the present invention. In the pulverization process, the subcomponents are homogenized so that there is no bias in the concentration. An organic binder such as polyvinyl alcohol is added to the obtained pulverized powder, and granulated using a spray dryer or the like to obtain a granulated powder. Furthermore, the granulated powder is filled into a mold of a predetermined shape and molded to obtain a molded body. The resulting compact is fired at about 1100 to 1400° C. to obtain MnZn ferrite.
[0051] The MnZn ferrite thus obtained has a high incremental permeability of 2300 or more in a wide temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied, and also has a high incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125°C.
[0052] (Improvement of variability) Conventional MnZn-based ferrite for pulse transformers requires a low upper limit temperature of 85°C, and high initial permeability and high incremental permeability, so compositions with high ZnO molar ratio and high initial permeability are often used. It is generally known that Zn is easily evaporated when fired at high temperatures. When a small ferrite core is molded and fired using ferrite powder with high initial permeability (high ZnO molar ratio), evaporation of Zn from the core surface is often considered a problem. The composition of the ferrite core surface is slightly different from that of the ferrite core interior due to the evaporation of Zn. Therefore, when ferrite powder with a high ZnO molar ratio is used, the variation in the composition of the surface becomes large, which causes a problem of large variation in the initial permeability and incremental permeability. In contrast, the MnZn-based ferrite of the present invention uses a composition with a high Curie temperature (low ZnO molar ratio) so that it can be used in a wide temperature range of -50°C to 150°C. In this way, when using ferrite powder with a low ZnO molar ratio, the evaporation of Zn from the ferrite core surface is suppressed, so the composition difference between the core surface and the inside is small, and the variation in initial permeability and incremental permeability is also small. The ferrite of the present invention has a composition with a low ZnO molar ratio compared to conventional MnZn-based ferrites for pulse transformers, and therefore has the advantage of smaller variation in magnetic properties. EXAMPLES
[0053] The raw powders of Fe2O3, ZnO, and Mn3O4 (composition ratio converted to MnO) which are basic components of MnZn ferrite were weighed so as to have the composition ratios shown in Tables 1 to 3. All raw powders were high purity raw powders. These raw powders were mixed and ground in a ball mill for 16 hours, and then calcined in air at 925°C for 3 hours to obtain calcined powders. Next, SiO2, CaCO3, Co3O4, TiO2, and Nb2O5 were added to the calcined powder so as to have the contents shown in Tables 1 to 3, and in some examples shown in Table 3, V2O5 was further added, and the powders were ground in a ball mill for 12 hours to obtain pulverized powders. Next, polyvinyl alcohol was added to the pulverized powder, granulated, and a toroidal core was formed by applying a pressure of 118 MPa. Thereafter, this compact was placed in a sintering furnace and sintered at a maximum temperature of 1350° C. to obtain a sintered sample (ferrite core) having a total dimension of 30.5 mm×inner diameter 19 mm×height 6.5 mm.
[0054] Each ferrite core thus obtained was wound with 20 turns, and the magnetic properties were measured using a precision LCR meter E4980A (manufactured by Keysight Technologies). The initial permeability (no DC magnetic field applied: 0 A / m) was measured at 23°C and a frequency of 100 kHz. The incremental permeability (DC magnetic field applied: 25 A / m) was measured at temperatures of -50°C, 0°C, 23°C, 50°C, 100°C, and 150°C and a frequency of 100 kHz. Tables 1 to 3 show the measurement results, and Figures 1A, 1B, 2A to 2E, and 3 show graphs of the measurement results.
[0055] Similarly, ferrite cores were produced by changing the amounts of CaO and V2O5 added, as shown in Table 4. Table 4, Figures 4A and 4B show the results of measuring the incremental permeability at a frequency of 100 kHz at temperatures of -50°C, 0°C, 23°C, 50°C, 75°C, 100°C and 125°C while applying a DC magnetic field of 50 A / m.
[0056] The contents of P, B, S, Cl, K and other unavoidable impurities were quantified according to JIS K 0102 (ICP mass spectrometry) and confirmed to be 500 mass ppm or less in total. The measurement results are shown in each table.
[0057] [Table 1]
[0058] [Table 2]
[0059] [Table 3]
[0060] [Table 4]
[0061] From the results of Examples 1 to 10 and Comparative Examples 1 to 4 shown in Table 1 and FIGS. 1A and 1B, it can be seen that if the basic composition of Fe is 52.0 mol% or more and 53.6 mol% or less in terms of Fe2O3, and Zn is 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, an incremental permeability of 2,300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0062] From the results of Examples 11 to 15 and Comparative Examples 5 and 6 shown in Table 2 and FIG. 2A, it can be seen that if the subcomponent Si is 30 mass ppm or more and 200 mass ppm or less in terms of SiO2, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0063] From the results of Examples 11 and 16 to 19 and Comparative Examples 7 and 8 shown in Table 2 and FIG. 2B, it can be seen that if the auxiliary component Ca is 300 mass ppm or more and 1000 mass ppm or less in terms of CaO, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0064] From the results of Examples 11 and 20 to 23 and Comparative Examples 9 and 10 shown in Table 2 and FIG. 2C, it can be seen that if the auxiliary component Co is in the range of 2100 mass ppm or more and 3500 mass ppm or less in terms of Co3O4, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0065] From the results of Examples 11 and 24 to 26 and Comparative Examples 11 and 12 shown in Table 2 and FIG. 2D, it can be seen that if the subcomponent Ti is in the range of 2500 mass ppm or more and 4000 mass ppm or less in terms of TiO2, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0066] From the results of Examples 11 and 27 to 30 and Comparative Examples 13 and 14 shown in Table 2 and FIG. 2E, it can be seen that if the auxiliary component Nb is in the range of 50 mass ppm or more and 500 mass ppm or less in terms of Nb2O5, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.
[0067] From the results of Examples 31 to 35 and Comparative Example 15 shown in Table 3 and FIG. 3, it is found that if the auxiliary component V is 500 mass ppm or less in terms of V2O5, an incremental permeability of 2,300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied, and that the addition of V2O5 provides a higher incremental permeability in both low and high temperature ranges than the case where V2O5 is not added.
[0068] From the results of Examples 36 to 39 and Comparative Example 16 shown in Table 4 and FIG. 4A, it can be seen that when the auxiliary component Ca is 300 mass ppm or more and 1000 mass ppm or less in terms of CaO, an incremental permeability of 1000 or more can be obtained at 125° C. when a DC magnetic field of 50 A / m is applied.
[0069] From the results of Examples 39 to 46 and Comparative Example 17 shown in Table 4 and FIG. 4B, it is found that if the auxiliary component V is 500 mass ppm or less in terms of V2O5, an incremental permeability of 1000 or more can be obtained at 125°C when a DC magnetic field of 50 A / m is applied, and that the addition of V2O5 results in a higher incremental permeability at 125°C than when no V2O5 is added.
[0070] (Example: Variation study) For Example 47 and Comparative Example 18 shown in Table 5, ferrite pulverized powder was prepared in the same manner as described above, polyvinyl alcohol was added to the pulverized powder to granulate, and a pressure of 118 MPa was applied to form a toroidal core to obtain a compact. The compact was then placed in a sagger and charged into a sintering furnace, and sintered at a maximum temperature of 1350°C to produce 100 sintered samples (cores) with an outer diameter of 6.0 mm, an inner diameter of 3.0 mm, and a height of 4.0 mm. For each of the obtained cores, the initial permeability at 23°C and the incremental permeability when a DC magnetic field of 25 A / m was applied at -40°C were measured by the above-mentioned method, and the standard deviation σ of each was calculated from the measurement results. Table 5 shows the magnetic properties (initial permeability and incremental permeability, which are the average values of the 100 measured values) and the standard deviation σ.
[0071] Here, Comparative Example 18 had the same components as Sample No. 1-5 (an invention example of Patent Document 1) in Patent Document 1. Note that although there is a difference in the initial permeability between Invention Example 47 and Comparative Example 18, they have almost the same incremental permeability when a DC magnetic field of 25 A / m is applied at -40°C.
[0072] [Table 5]
[0073] As shown in Table 5, in the case of Example 47, the standard deviation σ is smaller for both the initial permeability at 23° C. and the incremental permeability when a DC magnetic field of 25 A / m is applied at -40° C. than for Comparative Example 18. This shows that the composition of the present invention with a low ZnO molar ratio has smaller variations in magnetic properties and is more preferable than the conventional composition with a high ZnO molar ratio. [Industrial Applicability]
[0074] According to the present invention, it is possible to obtain MnZn-based ferrite that has a high incremental permeability over a wide temperature range, i.e., an incremental permeability of 2300 or more when a direct current magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C, which is suitable for electronic components such as pulse transformers. Also, it is possible to obtain MnZn-based ferrite that has an incremental permeability of 1000 or more when a direct current magnetic field of 50 A / m is applied at 125°C. This makes it possible to accommodate automotive applications and PoE power supply applications that require a wider temperature range than conventional applications.
Claims
1. An MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are Fe 2 O 3 The total of Fe, Zn, and Mn calculated as ZnO and MnO is 100.0 mol%, Fe:Fe 2 O 3 Converted to 52.6 mol % or more and 53.6 mol % or less, Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si:SiO 2 Converted to 30 ppm by mass or more and 200 ppm by mass or less, Ca: 300 ppm by mass or more and 1000 ppm by mass or less in terms of CaO; Co: Co 3 O 4 Converted to 2100 ppm by mass or more and 3500 ppm by mass or less, Ti: TiO 2 Converted to 2500 ppm by mass or more and 4000 ppm by mass or less, Nb: Nb 2 O 5 50 ppm by mass or more and 500 ppm by mass or less in terms of total mass, and V: V 2 O 5 Converted to 0 ppm by mass or more and 500 ppm by mass or less MnZn-based ferrite consisting of
2. An MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are Fe 2 O 3 The total of Fe, Zn, and Mn calculated as ZnO and MnO is 100.0 mol%, Fe:Fe 2 O 3 Converted to 52.0 mol % or more and 53.6 mol % or less, Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si:SiO 2 Converted to 30 ppm by mass or more and 200 ppm by mass or less, Ca: 300 ppm by mass or more and 1000 ppm by mass or less in terms of CaO; Co: Co 3 O 4 Converted to 2100 ppm by mass or more and 2700 ppm by mass or less, Ti: TiO 2 Converted to 2500 ppm by mass or more and 4000 ppm by mass or less, Nb: Nb 2 O 5 50 ppm by mass or more and 500 ppm by mass or less in terms of total mass, and V: V 2 O 5 Converted to 0 ppm by mass or more and 500 ppm by mass or less MnZn-based ferrite consisting of
3. An MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are Fe 2 O 3 The total of Fe, Zn, and Mn calculated as ZnO and MnO is 100.0 mol%, Fe:Fe 2 O 3 Converted to 52.6 mol % or more and 53.6 mol % or less, Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, and Mn: remainder and With respect to the basic component, the subcomponent is Si:SiO 2 Converted to 30 ppm by mass or more and 200 ppm by mass or less, Ca: 300 ppm by mass or more and 1000 ppm by mass or less in terms of CaO; Co: Co 3 O 4 Converted to 2100 ppm by mass or more and 2700 ppm by mass or less, Ti: TiO 2 Converted to 2500 ppm by mass or more and 4000 ppm by mass or less, Nb: Nb 2 O 5 50 ppm by mass or more and 500 ppm by mass or less in terms of total mass, and V: V 2 O 5 Converted to 0 ppm by mass or more and 500 ppm by mass or less MnZn-based ferrite consisting of
4. V 2 O 5 The MnZn-based ferrite according to any one of claims 1 to 3, wherein the content of V in terms of vanadium is 50 ppm by mass or more and 250 ppm by mass or less.
5. V 2 O 5 The MnZn-based ferrite according to any one of claims 1 to 3, wherein the content of V in terms of vanadium is 100 ppm by mass or more and 500 ppm by mass or less.
6. 4. The MnZn-based ferrite according to claim 1, wherein the incremental permeability is 2300 or more when a direct current magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C.
7. 5. The MnZn-based ferrite according to claim 4, wherein the incremental permeability is 2300 or more when a direct current magnetic field of 25 A / m is applied in a temperature range of −50 to 150° C.
8. 4. The MnZn-based ferrite according to claim 1, wherein the incremental permeability when a DC magnetic field of 50 A / m is applied at 125° C. is 1000 or more.
9. 6. The MnZn-based ferrite according to claim 5, which has an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125°C.
Citation Information
Patent Citations
Wide-temperature-range ultralow-power-consumption manganese-zinc ferrite material and preparation method thereof
CN112707723A
Ferrite sintered compact and method for producing the same
JP2009227554A
Ferrite composition, electronic component, and power supply device
JP2021161007A
Ferrite composition, electronic component and power supply
JP2022156991A
MnZn ferrite
JP7580014B1